How Frauds in Times of Crisis Target People - Taodang, Dean (Victims & offenders, 2023)
While there are no new frauds, internet technology provides new opportunities for fraudsters by facilitating volumes of attacks that law enforcement then struggles to address. Moreover, since context can affect how potential victims respond to frauds, crisis context influences how fraudsters design frauds. This article assesses fraudsters’ fraud design strategies during two external crisis events that impacted Australia: The Black Summer Bushfires that occurred from September 2019 to March 2020 and the onset and first year of the COVID-19 pandemic that occurred from January 2020 through January 2021. Targets, during these crises, were more likely to be vulnerable according to Steinmetz’s model victim for social engineering framework. This study shows that, in both crises, fraudsters deployed the social engineering techniques of “authority” and “scarcity,” techniques that are more likely to be successful based solely on initial contact. Fraudsters designed their requests to be easily actioned and crafted their scams to reference very recent events as the external crisis events evolved. Thus, they targeted broad audiences with minimal personal involvement. Furthermore, this study shows that fraudsters, when disseminating their scams via social media outlets, attempted to build “social proof” to expand their potential victim pool to include the marks’ social circles.